Fun hijaiyah - Rohaimi, Nur Miftah Jannah; Omar Sidik, Nur Farhana; Ismail, Mashitah; Hamzah, Nurain Fatin; Selamat, Nordibradini (Universiti Teknologi MARA, Kedah, 2018)
Fun Hijaiyah is a box full with surprise that can attract children to learn in a fun way. The box is purposely created for children age 3-9 years old. This box aimed to educate children in learning hijaiyah letters, while developing the moto skills and sensory skills. This box contains many games such as hijaiyah arrangement in order combining letters based on words, tin can number bowling, rhythm hijaiyah drum, color sorting and hijaiyah ring toss. Fun Hijaiyah box is made from box, felt, cloth, card paper, coloring A4 paper, Paper plate, Ping pong ball, cotton, and plastic cup. Novelty and Uniqueness: 1. Learn hijaiyah letters through games and interactive learning. 2. Games s are added to learn hijaiyah. 3. Sensory and motor skills developments are included to build the children skills while learning. 4. The materials and learning way is touchable.